Chapter Prendersi cura del mondo - McGilchrist, Iain (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
Discusses the role that attention plays in constituting the world, rather than reducing phenomena to the brain level. Discusses the different kinds of attention delineated by the divided hemispheres of the brain. On the one hand the left hemisphere specialised in grasping and manipulating the world, whereas the right hemisphere specialises in relat-ing to and understanding the world. Discusses how reliance on one or the other kind of attention has cultural, psychological and social implications.